2018
DOI: 10.1253/circj.cj-18-0136
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Electrocardiography in Patients With Fulminant Myocarditis Supported by Percutaneous Venoarterial Extracorporeal Membrane Oxygenation ― Analysis From the CHANGE PUMP Study ―

Abstract: on behalf of the CHANGE PUMP InvestigatorsBackground: Fulminant myocarditis (FM) presents various abnormal findings on ECG, the prognostic impact of which has not been not fully elucidated. The aim of this study was therefore to clarify the prognostic value of ECG data in FM patients supported by venoarterial extracorporeal membrane oxygenation (VA-ECMO). Methods and Results:In this multicenter chart review, we investigated 99 patients with FM supported by VA-ECMO. The final cohort consisted of 87 patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
3
19
0
1
Order By: Relevance
“…CRRT and ECMO remove some of the cytokines from the blood and increase blood oxygen saturation, reducing the excessive immune response of cytokines in the body and further reducing myocardial damage. Furthermore, a study showed that complete atrioventricular block, ventricular tachycardia, and fibrillation are risk factors for in-hospital death in fulminant myocarditis patients [14]. The absence of such electrocardiogram anomalies in this case may have contributed to the rapid improvement in the patient's heart condition, and the prognosis of this patient may have been better if secondary infection could have been controlled.…”
Section: Discussionmentioning
confidence: 71%
“…CRRT and ECMO remove some of the cytokines from the blood and increase blood oxygen saturation, reducing the excessive immune response of cytokines in the body and further reducing myocardial damage. Furthermore, a study showed that complete atrioventricular block, ventricular tachycardia, and fibrillation are risk factors for in-hospital death in fulminant myocarditis patients [14]. The absence of such electrocardiogram anomalies in this case may have contributed to the rapid improvement in the patient's heart condition, and the prognosis of this patient may have been better if secondary infection could have been controlled.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, a study shows complete atrioventricular block, ventricular tachycardia or fibrillation are risk factors for in-hospital death in fulminant myocarditis patients. Extensive QRS waves also predict poor outcomes in such cases[12]. The absence of such electrocardiogram anomaly in this case may have contributed to the rapid improvement in the patient's heart condition.ConclusionCOVID-19 patients may develop severe cardiac complications such as myocarditis and heart failure, and this is the first case of COVID-19 that is complicated with fulminant myocarditis.…”
mentioning
confidence: 66%
“… 9 Cytokine storms may lead to increased vascular wall permeability and myocardial oedema. 10 However, in view of the patient’s rapid recovery, low increase of C-reactive protein, and the early presentation of the acute myocarditis, myocardial injury was considered to be transient damage from viral infection rather than from the cytokine storm. In addition, the clinical outcome of the patient was favourable, without use of corticosteroids, antiviral drugs, or chloroquine.…”
Section: Discussionmentioning
confidence: 99%